2008
DOI: 10.1002/j.1551-8833.2008.tb09704.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hypochlorite dosage for household and emergency water treatment

Abstract: Point‐of‐use (POU) water treatment with sodium hypochlorite (NaOCl) has been proven to reduce diarrheal disease in developing countries. However, program implementation is complicated by unclear free chlorine residual guidelines for POU water treatment and difficulties in determining appropriate dosage recommendations. The author presents evidence supporting proposed criteria for household water treatment for free chlorine residuals of < 2.0 mg/L 1 h after NaOCl addition and > 0.2 mg/L after 24 h of storage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 17 publications
1
55
0
2
Order By: Relevance
“…Only 10 (3.3%) samples were 10 NTU, indicating the need for double chlorine dosage, filtration before disinfection, or more frequent cleaning of filters. 23 The average turbidity of 155 untreated water samples tested in the recovery evaluation was 3.8 NTU (minimum = 0, maximum = 46), with only 15 (9.7%) samples 10 NTU.…”
Section: Resultsmentioning
confidence: 95%
“…Only 10 (3.3%) samples were 10 NTU, indicating the need for double chlorine dosage, filtration before disinfection, or more frequent cleaning of filters. 23 The average turbidity of 155 untreated water samples tested in the recovery evaluation was 3.8 NTU (minimum = 0, maximum = 46), with only 15 (9.7%) samples 10 NTU.…”
Section: Resultsmentioning
confidence: 95%
“…15 There is an extensive literature demonstrating the efficacy of POU chlorination of household drinking water in reducing the incidence of pediatric diarrheal diseases. 14,16 However, previous studies have also found that the effectiveness of chlorine in reducing microbial contamination can vary based on source-water turbidity, source-water baseline contamination levels, and in-home contamination. 16,17 In rural Ecuador, only 17% of households with high source-water turbidity (> 10 NTU) were able to achieve the World Health Organization guideline for safe drinking water after chlorine treatment with a sodium hypochlorite (NaOCl) solution of 1.875 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Only two evaluations measured both reported and confirmed use (Lantagne andClasen 2012, Colindres et al 2007) (Table 17). Documents with both measures, reported use ranged between 6-22% and confirmed use ranged [4][5][6][7][8][9][10][11][12].…”
Section: Combination Flocculant/disinfectantsmentioning
confidence: 85%
“…The amount of organic content and withdrawn water also impact the amount of chlorine needed for treatment. Ideally, the FCR for water treatment would be greater than or equal to 0.2 mg/L and less than or equal to 2.0 mg/L -which is the range ensuring water treatment but not exceeding taste or guideline thresholds (Lantagne 2008). Six documents were identified in the review evaluating well disinfection.…”
Section: Well Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation